2013
DOI: 10.1111/wrr.12083
|View full text |Cite
|
Sign up to set email alerts
|

Local blockade of glucocorticoid activation reverses stress‐ and glucocorticoid‐induced delays in cutaneous wound healing

Abstract: Stress slows cutaneous wound healing (WH) in an endogenous glucocorticoid (GC)-dependent fashion. We investigated whether stress/GC-induced delays in WH require further intracutaneous activation of endogenous GC; and whether blockade or down-regulation of peripheral activation normalizes WH in the face of stress. Delayed WH in our motion-restricted murine model of stress could be attributed to elevated systemic GC, because blockade of GC production (using corticotropin-releasing factor inhibitor, antalarmin), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 41 publications
2
33
0
1
Order By: Relevance
“…Evidence of the deleterious effects of chronic GR overexpression and activation suggests that a selective GR antagonist would be a useful adjunct to the treatment of stress-related cognitive disorders (90, 236), as well as systemic problems as diverse as cardiometabolic syndromes (220) and wound healing (497), but to date there is none, in great measure due to the homologies of the LBDs of steroid receptors, as discussed above. RU-486, mifepristone, initially developed in search of a GR antagonist, is also a potent antagonist of the progesterone receptor.…”
Section: Mammalian Adrenocorticosteroids and Their Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence of the deleterious effects of chronic GR overexpression and activation suggests that a selective GR antagonist would be a useful adjunct to the treatment of stress-related cognitive disorders (90, 236), as well as systemic problems as diverse as cardiometabolic syndromes (220) and wound healing (497), but to date there is none, in great measure due to the homologies of the LBDs of steroid receptors, as discussed above. RU-486, mifepristone, initially developed in search of a GR antagonist, is also a potent antagonist of the progesterone receptor.…”
Section: Mammalian Adrenocorticosteroids and Their Receptorsmentioning
confidence: 99%
“…Limited early trials with selective 11β-HSD1 antagonists improved glycemic control in obese type 2 diabetics (20, 219, 466). Selective 11β-HSD1 antagonists may also accelerate wound healing by decreasing GR-mediated effects that impede MR trophic and fibrotic repair effects (473, 497). Epigenetic events during gestation and early childhood related to growth restriction and/or stress increase the relative expression of 11β-HSD1:11β-HSD2 and are associated with cardiometabolic risk in the adult (81, 220, 375, 484).…”
Section: Pathophysiological Implications Of Inappropriate Mr Activationmentioning
confidence: 99%
“…11βHSD1 deficiency is also associated with enhanced angiogenesis in ischaemic tissues, resulting, for example, in improved left ventricular function following myocardial infarction in mice and potentially improving wound healing [97,98], a common problem in diabetes. Increased 11βHSD1 activity in ageing human fibroblasts leads to skin ageing and impaired wound healing, and topical application of an 11βHSD1 inhibitor improves wound healing in humans [99,100].…”
Section: Outstanding Challengesmentioning
confidence: 99%
“…We previously reported that 11␤-HSD1 and H6PDH were expressed in the rat brain, including the whole hypothalamus (48); however, we did not study their colocalization within individual neurons essential for prereceptor modulation of a ligand and crucial global effects, even when expressed in a small number of neurons, as shown by Geerling et al (26). It has been postulated that the use of selective 11␤-HSD1 inhibitors would alleviate obesityand age-related maladies from cardiometabolic syndrome to dementia and problems with wound healing (55,59,110). However, the present findings suggest caution.…”
Section: Discussionmentioning
confidence: 88%